1993
DOI: 10.1128/iai.61.1.155-161.1993
|View full text |Cite
|
Sign up to set email alerts
|

Release of cytokines induced by Salmonella typhimurium porins

Abstract: Salmonella typhimurium SH5014 porins induce the release of tumor necrosis factor alpha (TNF-), interleukin lee (IL-la), and IL-6 by human monocytes and of gamma interferon (IFN-y) and ILH4 by human lymphocytes. Porins at 1 ,ug/ml induce the greatest release of TNF-a, IL-let, and IL-6 by monocytes and of I]LA by lymphocytes, while porins at 5 ,ug/ml induce the greatest release of IFN-y by lymphocytes. The R form of lipopolysaccharide (LPS-R) induces the greatest release of TNF-a and IL-lee by monocytes when use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
50
1
2

Year Published

1995
1995
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(57 citation statements)
references
References 48 publications
4
50
1
2
Order By: Relevance
“…The binding of S. typhimurium porins to human polymorphonuclear leukocytes induces a decreased oxidative burst in these cells as well as inhibits their migration in the presence of chemotactic agents [32]. Salmonella typhimurium porins bind to the membranes of polymorphonuclear leukocytes [33]; moreover, they incorporate into MÖ membranes [34]. Subcellular events in macrophages following attachment of the 44-kDa protein have not yet been characterized.…”
Section: -Kdamentioning
confidence: 99%
“…The binding of S. typhimurium porins to human polymorphonuclear leukocytes induces a decreased oxidative burst in these cells as well as inhibits their migration in the presence of chemotactic agents [32]. Salmonella typhimurium porins bind to the membranes of polymorphonuclear leukocytes [33]; moreover, they incorporate into MÖ membranes [34]. Subcellular events in macrophages following attachment of the 44-kDa protein have not yet been characterized.…”
Section: -Kdamentioning
confidence: 99%
“…Since the mid-1980s, a major OMP of Salmonella has been the subject of much investigation, and our earlier work has shown that porins afford protection against Salmonella infection [6][7][8][9]. Several workers have demonstrated porins to be important antigens, which elicit CMI responses through a delayed-type hypersensitivity reaction, interleukin-2 (IL-2) and interferon-g (IFN-g) production, and mitogenic effects on T and B cells [4,10]. Porins also activate the complement system and contribute to the pathogenesis of the bacterial infection [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…The stimulation of CMI by porin immunization could be due to the amphiphilicity and amount of this protein, or to its intrinsic immunogenicity. Porins induce lymphocytes to secrete IL-2 and IFN-y ( [4,9] and not shown), and IFN-y can initiate macrophage effector activities in vitro. Certainly, the antigen-activated T cells could be involved at least as a source of IFN-y in this cascade, and presently, it is hypothesized that macrophages could be activated by soluble TNF-a and IFN-y secreted by Thl cells, secreted IFN-y and membranebound TNF-a and by cognate interactions [28].…”
Section: Discussionmentioning
confidence: 99%